Adiponectin resistance in skeletal muscle: pathophysiological implications in chronic heart failure. Issue 3 (27th October 2015) - Sente, Tahnee; Van Berendoncks, An M; Hoymans, Vicky Y; Vrints, Christiaan J
Abstract: Skeletal muscle wasting is a common complication of chronic heart failure (CHF) and linked to poor patient prognosis. In recent years, adiponectin was postulated to be centrally involved in CHF‐associated metabolic failure and muscle wasting. This review discusses current knowledge on the role of adiponectin in CHF. Particular emphasis will be given to the complex interaction mechanisms and the intracellular pathways underlying adiponectin resistance in skeletal muscle of CHF patients. In this review, we propose that the resistance process is multifactorial, integrating abnormalities emanating from insulin signalling, mitochondrial biogenesis, and ceramide metabolism.